The long-run relationship between economic growth, financial development, trade openness and CO2 emissions in Malaysia - Ali, W. (Institute of Electrical and Electronics Engineers Inc., 2015)
The proposed study will investigate the relationship between the carbon dioxide and its determinants like economic growth, financial development and trade openness for a time period 1970-2012. Theoretical and empirical contradictions in literature exists on the relationship between the variables of the study, but these variables are still very important in determining the CO2 emissions. In line with the Environmental Kuznets Curve (EKC) hypothesis it is expected that economic growth will improve environmental quality in the long-run. Similarly, it is hypothesized that financial sector development will reduce the CO2 emissions which will lead to the betterment in quality of environment in case of Malaysia during the study period. It is supposed that increase in the imports of the country will focus on the environmental friendly technology and openness will decrease the level of pollution. The relationship and impact of the variables is unclear and controversial in different case studies and also panel studies, which make it a center of discussion for further research. The proposed study will employ vector error correction model (VECM) approach to investigate the relationship between the variables. For the robustness of results it is suggested to employ impulse response function (IRF) and variance decomposition (VD). Â© 2015 IEEE.